Instagram Use and Self-Esteem among Adolescents - Evelin; Made Syanesti Adishesa (Jurnal Ilmiah Psikologi MIND SET, 2020)
Photo-based social media like Instagram is popular in young people. But despite its fame, Instagram proved to be a social media that has the worst impact on adolescent’s mental health. One of the negative impact that may result from using social media is a decrease in self-esteem, which is an individual’s evaluation or judgement about himself. In addition, self-esteem has also proven to be a predictor of excessive use of Instagram in adolescents. This study aims to examine the relationship between the intensity of Instagram usage and self-esteem on adolescents. This study was conducted with quantitative methods, correlational analysis. The number of participants is 410 teenagers aged 12 to 21 years (M = 15.38, SD = 1.71), obtained using convenience sampling techniques. The result showed negative correlation between Instagram use and self-esteem. This indicates that the higher the intensity of using Instagram, the lower the self-esteem. Moreover, further analysis indicates different gender and activities in Instagram may have different relation to self-esteem. Implications of this study in adolescent use of Instagram were discussed.